Key Factors of Employee Performance and Sustainable HR Practices in Indonesian Manufacturing Industry - Suprayitno, Degdo (Yayasan Sinergi Kawula Muda, 2024)
In the framework of Indonesia's manufacturing sector, this study explores the complex relationships that exist between social media use, employee performance, recruiting, retention, and sustainable HR practices. A thorough quantitative research yielded insights into these links for a sample of 220 participants spanning various organizational levels. The study used partial least squares (SEM-PLS) structural equation modeling to investigate the direct and indirect relationships between the constructs. The findings show that social media use, hiring, and retention have a substantial beneficial direct impact on worker performance. Furthermore, an indirect effect was found, which shows that social media usage done well influences sustainable HR practices by mediating employee performance. The results provide firms looking to improve employee performance and promote sustainable HR practices in the ever-changing Indonesian manufacturing industry with practical takeaways.